2020
DOI: 10.1021/acs.iecr.0c00084
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Selection of the Post-Treatment Strategy for ZSM-5 Zeolites for the Improvement of Catalytic Stability in the Conversion of Methanol to Hydrocarbons

Abstract: Desilication and dealumination are two common strategies to modify acidity and porosity of the ZSM-5 catalyst to enhance catalytic stability. However, the applicability of these strategies on the post treatment of specific ZSM-5 remains to be investigated. In this paper, a series of post-treated nano-ZSM-5 was prepared using single dealumination and desilication or combining two strategies and the effects of the silicon–aluminum structure, porosity, and acidity on catalytic stability of methanol to hydrocarbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Z4: it is a conventional hydrothermal synthesis method, according to the literature 36 crystallizing a gel with a molar composition of 36SiO 2 : NaAlO 2 : 9.0TPAOH : 5.0NaOH : 144EtOH : 300H 2 O at 170 °C for 48 h, which was used for comparison with our protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Z4: it is a conventional hydrothermal synthesis method, according to the literature 36 crystallizing a gel with a molar composition of 36SiO 2 : NaAlO 2 : 9.0TPAOH : 5.0NaOH : 144EtOH : 300H 2 O at 170 °C for 48 h, which was used for comparison with our protocol.…”
Section: Methodsmentioning
confidence: 99%
“…35 Then sodium aluminate, sodium hydroxide, and fumed silica were added to the liquid seed in the same way as that of Z1 but retaining the final molar ratio of the solid mixture. Finally, the solid mixture was crystallized at 90 °C for b h. Z4: it is a conventional hydrothermal synthesis method, according to the literature 36 crystallizing a gel with a molar composition of 36SiO 2 : NaAlO 2 : 9.0TPAOH : 5.0NaOH : 144EtOH : 300H 2 O at 170 °C for 48 h, which was used for comparison with our protocol.…”
Section: Zeolite Synthesismentioning
confidence: 99%
“…It can be concluded that the H-ZSM-5 catalyst is preferred for both reaction zones. The activity and selectivity over H-ZSM-5 zeolite further depends on its acidity (the Si/Al ratio), which can be varied by partial ion-exchange with Ca [17] or via postsynthesis treatments [18]. Yet the internal diffusion of bulky molecules is hindered in microporous zeolites; therefore, only active sites located in the channels close to the crystal outer surface are accessible for the reactants.…”
Section: Application Of Structured Catalysts and Reactorsmentioning
confidence: 99%
“…It is generally accepted that Brønsted acid sites of zeolites are the active centers for the conversion of olefins to aromatics. However, this type of catalyst suffers from rapid deactivation during the aromatization reaction [9].…”
Section: Introductionmentioning
confidence: 99%